To study problematic eating behavior and its association with early childhood caries among 36-71-month-old children using children eating behavior questionnaire - Neha Charak; Anuradha Pathak; Haridarshan Singh Sidhu (Wolters Kluwer Medknow Publications, 2021)
Context: Problematic eating behavior pattern prevalent in children can be a potential risk factor for Early Childhood Caries (ECC). Pediatric dentist must be vigilant to enquire about eating behavior pattern and guide parents comprehensively. Aim: The aim of this study is to find the association between problematic ECC among 36-71-month-old children. Setting and Design: A cross-sectional study was conducted in 2000 children from both the sex and various socioeconomic backgrounds. Methods: A questionnaire was made to assess the personal information and problematic eating behavior of the child using Children's Eating Behavior Questionnaire (CEBQ) which was filled by parents. Clinical examinations were performed on the date of questionnaire collection and caries diagnosis was done in the dentition status part of "WHO oral health assessment form 2013." Statistical Analysis Used: The software used for the statistical analysis was SPSS (Statistical Package for the Social Sciences) software version 16.0. Results: The prevalence of ECC in the study sample was 42.6%. Out of eight domains into which problematic eating behavior was divided, domains Emotional Overeating (EOE), Satiety Responsiveness (SR), Slowness of Eating (SE), Desire to Drink, Food Fussiness, and Emotional Under eating were significantly associated with ECC. Conclusion: There is a positive correlation between problematic eating behavior and ECC; such behavior should be recognized at early stages and interrupted so that the risk of developing caries in permanent dentition could be prevented.